Education and Skill Development for Sustainable Rural Development - Sumit Jain (International Journal of Rural and Regional Development, 2024)
Leveraging education and skill development is a critical aspect of sustainable rural development enabling rural connected populations to gain knowledge and tools to enhance their economic opportunities, survive and thrive in changing environments and play its role in investment in rural development. This study analyzes the multiple functions of education and skill programs in rural areas, how they contribute to economic growth, social inclusion and environmental sustainability. Through focusing on skills that are relevant to enhance survival and rationalizing incomes such as sustainable agriculture, entrepreneurship and technical vocations for example, these programs provide hope for rural populations to diversify income and reduce dependence on traditional livelihoods. Communities also involved, local industries partnerships and supportive policies further enhance the program effectiveness and alignment with local needs. Which are still major challenges such as: limited infrastructure and funding. This research underlines the importance of community led, as opposed to top-down, education and skill development as critical components for rural areas achieving long-term sustainability and self-reliance, as part of broader aspirations for poverty alleviation and social equity
Keywords: Rural Development; economic empowerment; skill development; sustainable education